Risk approach to sanitary-andepidemiological assessment of the location of modern filling stations (Environment & Health, 2017)
The aim of the work was to determine indicators of the risk to public health from chemical pollution of the environment caused by emissions from filling stations of various capacities, with regard to the territorial characteristics of residential areas.Materials and methods. The methods of sanitary-and-hygienic examination of existing facilities, sanitary-and-epidemiological expertise of projects of sanitary protection zones of filling stations of various capacities, the methods of the risk assessment were used.Conclusions. The results show that the sanitary classification of enterprises and manufacturing requires revision and rationing of differentiated sanitary protection zones (minimum and maximum) for filling stations, taking into account their capacity, implementation of effective environmental protection measures, and applying of risk approach to sanitary-and-epidemiological assessment of filling stations.The necessity of introducing of equipment to contain carcinogenic fumes when refueling vehicles at existing and projected filling stations is proven. This will reduce the air pollution of the filling station’ working area and the environment of the adjacent residential area.
Keywords: filling station; sanitary-andepidemiological assessment; risk assessment; environment contamination